Analisis Wacana Kritis Sara Mills Berita Guru Mengaji di Aceh Utara Diduga Berkali-Kali Perkosa Santri Usia 15 Tahun - Rini Haryani; M. Surip; Syairal Fahmy Dalimunthe (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
This article focuses on the discourse of feminism, which describes how the position of women is expressed in the text. The news contained explaining the incident of rape on students carried out by the Quran teacher which was alleged to have been done repeatedly, the news became the material object of this research. Discourse analysis is a qualitative approach to analysis that considers the meaning of the text. Each text, in essence, can be understood differently, in various ways. Material objects are analyzed using the Sara Mills point of view. The result of the research shows that the perspective of women shows the weak position of women. Even though the incident was indeed carried out by the perpetrator based on the victim's testimony, it has an impact on the view or image of a woman who remains bad in the eyes of the reader even though it is a woman who is a victim.